Concentration of Orange Juice Using Forward Osmosis Membrane Process - W. Hameed, Khalid (Iraqi Journal of Chemical and Petroleum Engineering, 2013)
Forward osmosis (FO) process was applied to concentrate the orange juice. FO relies on the driving force generating from osmotic pressure difference that result from concentration difference between the draw solution (DS) and orange juice as feed solution (FS). This driving force makes the water to transport from orange juice across a semi-permeable membrane to the DS without any energy applied. Thermal and pressure-driven dewatering methods are widely used, but they are prohibitively energy intensive and hence, expensive. Effects of various operating conditions on flux have been investigated. Four types of salts were used in the DS, (NaCl, CaCl2, KCl, and MgSO4) as osmotic agent and the experiments were performed at the concentration of the salts in the DS ranged (3.5 – 20% by wt), the temperature of DS ranged (20 – 50oC), and the flow rate of the FS and DS ranged (1 – 4 lit/min). It was observed that the optimum operating conditions are: concentration of salt = 20% by wt for CaCl2, temperature of DS = 50oC, and the flow rate of FS = 4 lit/min where at these conditions the maximum flux was obtained equal to 13.2 lit/m2.h or the total volume of the water transferred from the juice (during 3 hours and membrane area of 0.0135 m2) was 0.535 lit. NaCl performed much higher efficiency as osmotic agent than the others salts up to the concentration of 15.2%, but after 15.2% the CaCl2 was the best.